Computational Investigation of the Cooling and Heating Effect in Vortex Tube - Duan, Dingli; Guan, Shuaibing; Qiao, Yanfeng; Wang, Jay (ASME International, 2026)
Vortex tubes exhibit a unique temperature separation phenomenon, leading to their widespread application in refrigeration and heating. Using the exact flow and temperature field simulation, this study examined the cooling effect and heating effect under different cold mass fractions, inlet pressure and diameter ratios. The cooling effect shows a trend of first increasing and then decreasing with the increase of the cold mass fractions while the heating effect gradually increases. Actually, the cooling and heating effect are suppressed by backflow, it is difficult for the working fluid to flow out of the cold end leading to the backflow at the cold end is severe at low cold mass fractions, and the reverse flow boundary exceeds the control valve causing the backflow at the hot exit is enhanced at high cold mass fractions. In order to get excellent cooling effect and heating effect of the vortex tube, the inlet pressure should be increased while reducing the diameter ratio of the vortex tube, and the cold mass fractions should be controlled within a reasonable range (CMF=0.3∼0.7).
Keywords: 4012 Fluid mechanics and thermal engineering; Evaporation; Heat and Mass Transfer; Heat Exchangers; Heat Transfer Enhancement; Thermophysical Properties